Temperature of projectile fragment emission source in fragmentation of $$^40$$Ar at 500 A MeV - Li, Rong; Dang, Ying-Hua; Kang, Jing-Xiao; Li, Jun-Sheng; Zhang, Dong-Hai (Journal of the Korean Physical Society, 2025)
The emission angular distributions, the transverse momentum distributions, and the temperature parameters of projectile fragments produced in fragmentation of 40 Ar on Al and Cu targets at 500 A MeV are investigated using the solid nuclear track detector CR-39. It is found that the mean value and the width of the angular distribution are increased with the decrease of the charge of projectile fragments. The cumulative squared transverse momentum distribution of projectile fragments can be well fitted by a single Rayleigh distribution, which indicates that the projectile fragments are emitted from a single tem perature emission source. The temperatures of projectile fragments emission source are in the range of 2–10 MeV, increase with the decrease of the charge of the projectile fragments. KCI Citation Count: 0